Associations of first-trimester TMAO and its precursors with gestational diabetes mellitus: a pilot prospective cohort study - Chen, Geng-Dong; Pang, Ting-Ting; Li, Peng-Sheng; Ye, Shao-Xin; Gou, Xiao-Yan; Wang, Hai-Yan; Lin, Dong-Xin; Fan, Da-Zhi; Deng, Lu-Sha; Wang, Li-Juan; Zhou, Zi-Xing (Frontiers in Nutrition, 2025)
AimsWe aimed to provide a comprehensive understanding of the associations between Trimethylamine-N-oxide (TMAO), its precursor and gestational diabetes mellitus (GDM).MethodsIn this prospective study, 940 women were included in a Chinese single -center pregnant cohort. First trimester plasma concentrations of TMAO and its precursors (betaine, choline, L-carnitine, and trimethylamine) were measured using UPLC-ESI-MS/MS. GDM and specific abnormal glucose levels (fasting glucose; one-hour post-load glucose, 1-h PG; two-hour post load glucose, 2-h PG; and 1-h PG ≥ 8.6 mmol/L) were assessed through oral glucose tolerance tests. First-trimester plasma concentrations of TMAO and its precursors were divided into quartile groups (bottom, Q1; middle, Q2 and Q3; top, Q4).ResultsAmong the subjects, 167 (17.8%) were found to have GDM. After adjusting for potential covariates, the lower groups (Q1) of L-carnitine were associated with a higher risk of GDM compared to the reference group (middle quartiles). The OR (95% CI, p) was1.56 (1.04, 2.35, p = 0.032) for L-carnitine. Specifically, the associations were mainly derived from L-carnitine and abnormal 1-h PG. The ORs (95% CI, p) were 2.00 (1.24, 3.24, p = 0.005).ConclusionLow plasma levels (bottom vs. middle quartiles) of L-carnitine the first-trimester pregnancy were associated with a higher risk of GDM and abnormal 1-h PG in Chinese pregnant women.